The relationship of market oritentation and learning orientation with sme’s performance in the context of pakistan - Muhammad Hassan Arshad; Maha Mohammad Yusr Othman; Maruf ` Gbadebo Salimon (2020)
The small and medium-sized enterprises (SMEs) plays a crucial part in country’s economic growth and a key contributor in country’s GDP. In Pakistan SMEs hold about 90 percent of the total business. The performance of SMEs depends upon many factors. The main purpose of this research is to examine the relationship between Entrepreneurial Orientation and Market Orientation with SME’s Performance in Pakistan Conclusively, this study proposes a new research direction and proposition development to inspect the relationship among the variables in Pakistan’s SMEs context.